SAT0247 Safety of RAPID Rituximab Infusion in Rheumatoid Arthritis in A Single Community Practice. (10th June 2014) - Faraawi, R.; Malik, S.; Roth, K.
Abstract : Background: Rituximab, a chimeric monoclonal anti-CD20 antibody, is approved to be infused over 4hours and 15minutes, due to the potential for infusion reactions. The risk of infusion reactions has been shown to be greatest with the first infusion. Previously we reported our experience with rapid rituximab infusion in 10 rheumatoid arthritis patients, receiving a total of 26 rapid infusions. We now report a current safety analysis of 28 patients receiving a total of 132 rapid infusions in a single rheumatology practice. Objectives: To evaluate the safety, tolerability, and practicality of a rapid-infusion protocol for rituximab in RA patients (n=28) in a single community setting. Methods: Patients, who were prescribed Rituximab for treatment of moderate to severe RA, were recruited from October 2006 to November 2013 and given the opportunity to participate in the rapid infusion protocol. All patients provided written informed consent. Each treatment course consisted of two rituximab 1000mg infusions, give 2 weeks apart. The first infusion followed the conventional infusion schedule. Rapid infusion protocol was administered on second and/or all subsequent infusions over 2hours. All patients received premedication. Vital signs were recorded at baseline and at 15, 30, 60, 90 and 120minutes. Results: A total of 57 patients received rituximab infusions (280 infusions) from October 2006 to November 2013. Out of these, 50 patients with a diagnosis of rheumatoid arthritis met the criteria to be followed on the short infusion protocol. A total of 28 patients agreed to be followed on the rapid rituximab infusions. 132 infusions were included in this analysis with the mean treatment interval of 9.4 months. 93% of the patient population had failed or were intolerant to prior TNF-α inhibitors and 7% were biologic naïve. A total of 7 infusion reactions were reported over 132 rapid rituximab infusions (28 patients), as compared to 8 infusion reactions over 148 conventional infusions (22 patients). There was no significant difference in the incidence of infusion reactions between rapid and conventional infusion (p=0.97). In both rapid and conventional infusions, no patients discontinued rituximab due to infusion-related symptoms and reactions. Overall, all symptoms reported were mild and resolved within 24 hours after the infusion. No serious infections or serious adverse events were reported in both short and conventional infusion groups. Conclusions: The current analysis provides reassurance that rapid rituximab infusion is safe and well tolerated. Our experience of administering this protocol over seven years proves that rapid infusion is as safe as the conventional infusion. In addition to safety, patients reported greater satisfaction with the short infusion duration. These data and previously reported data on rapid infusion in rheumatoid arthritis patients assure physicians that this strategy can be safely implemented in an infusion clinic setting. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1206